Будова одного класу груп з умовами щільності нормальності для підгруп - Семко, М.М. (Український математичний журнал, 1997)
Конструктивно описані локально ступінчасті групи G, у яких для будь-якої пари підгруп A and B such that A таких, що A, існує нормальна підгрупа N із G і A≦N≦B. We give a constructive description of locally graded groups G satisfying the following condition: For any pair of subgroups A and B such that A<B, there exists a normal subgroup N that belongs to G and is such that A≦N≦B.